Penerapan Metode Penilaian Persediaan Barang Dagang Pada PT. Chemical Di Surabaya - Islami Islami; Sutini Sutini; Diana Zuhroh; Wiratna Wiratna; Tjandra Wasesa; Heri Toni Hendro P (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study aims to determine the application of the method of valuation of merchandise inventory at PT. Chemical that conform to generally accepted standards. The research method used in this study is descriptive qualitative. The types of data used in this study are quantitative data and qualitative data with collection techniques in the form of initial preliminary surveys, literature studies, observations, documentation, and interviews. The subject of this study was PT. Chemical, with the object under study is a method of valuing merchandise inventory at PT. Chemical. Researchers used inventory auxiliary book data for one of the trade goods from 2019 to 2021. The results showed that PT. Chemical does not apply the method of valuation of merchandise inventory, so the company cannot know the final value of merchandise inventory, gross profit, and cost of goods sold (COGS) of the company's merchandise. The inventory valuation method applied should be in accordance with the actual condition of the inventory of these trade goods in the company, considering that the goods sold are food chemicals with an expiration period of 2 to 3 years. PT. Chemical is advised to use the FIFO assessment method, because with this method in 2019-2021 the highest gross profit of other assessment methods was obtained, namely in 2019 of IDR 12,449,091, in 2020 of IDR 40,765,000, and in 2021 of IDR 19,880,000. The final inventory value with the FIFO assessment method also obtained the highest value, namely in 2019 of IDR 88,800,000, in 2020 of IDR 51,300,000, and in 2021 of IDR 23,730,000. The lowest value of goods sold was IDR 86,990,909 in 2019, IDR 329,240,000 in 2020, and IDR 228,090,000 in 2021.